2015
DOI: 10.1080/01621459.2015.1016226
|View full text |Cite
|
Sign up to set email alerts
|

A Regression Framework for Rank Tests Based on the Probabilistic Index Model

Abstract: We demonstrate how many classical rank tests, such as the Wilcoxon-MannWhitney, Kruskal-Wallis and Friedman test, can be embedded in a statistical modelling framework and how the method can be used to construct new rank tests. In addition to hypothesis testing, the method allows for estimating effect sizes with an informative interpretation, resulting in a better understanding of the data. Supplementary materials for this article are available online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…It is also showed that the estimatorβ is asymptotically normally distributed with a consistent estimator of its variance. We refer readers to [25], [8] and the supplementary file for further details about PIMs.…”
Section: Probabilistic Index Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also showed that the estimatorβ is asymptotically normally distributed with a consistent estimator of its variance. We refer readers to [25], [8] and the supplementary file for further details about PIMs.…”
Section: Probabilistic Index Modelsmentioning
confidence: 99%
“…We propose a semi-parametric method based on Probabilistic Index Models (PIM) [25,8], for testing DE in scRNA-seq data. PIMs entail a large class of semi-parametric models that can generate many of the traditional rank tests, such as the Wilcoxon-Mann-Whitney test and the Kruskal-Wallis test [25,8]. These models can be seen as the rank-equivalent of the generalized linear models (GLM).…”
Section: Introductionmentioning
confidence: 99%
“…Their interpretation is as follows: if p ij ⩽ p rs the observations under factor combination ( i , j ) tend to result in smaller values as the observations under factor combination ( r , s ). Moreover, another interpretation can be given in terms of additive effects by using a decomposition of the distribution functions as in Akritas and Arnold () and the supporting information in De Neve and Thas (): writingG=trueFfalse¯··=false(1false/abfalse)i=1aj=1bFij,Ai=trueFfalse¯i·G=false(1false/bfalse)j=1bFijG,Bj=trueFfalse¯·jG=false(1/afalse)i=1aFijGand(AB)ij=FijtrueFfalse¯i·trueFfalse¯·j+Gwe have F ij = G + A i + B j +( AB ) ij . Plugging this into the definition of the non‐parametric effect results in an additive effects representation as in classical linear modelsfalse0pij=GnormaldFij=12+GdAi+GdBj+Gd(AB)<...>…”
Section: Specific Designsmentioning
confidence: 99%
“…Recently, Fan and Zhang () have proposed a generalized estimating equations approach for rank‐transformed data and Thas et al . () and De Neve and Thas () have introduced the similar concept of the so‐called probabilistic index model (PIM). It allows flexible rank‐based modelling for various designs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation